A family cluster of diagnosed coronavirus disease 2019 (COVID‐19) kidney transplant recipient in Thailand. Issue 4 (8th August 2020) - Sakulkonkij, Parichart; Bruminhent, Jackrapong; Pankongngam, Charan; Chalermphunchai, Nipon
Abstract: Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) causes an ongoing outbreak of respiratory illness called coronavirus disease 2019 (COVID‐19). The clinical course could be ranging from mild to severe illness especially the individuals with an immunocompromised condition such as solid organ transplant recipients. Method: We described a family cluster of COVID‐19 patients who were admitted during 3rd April 2020 to 30th April 2020. COVID‐19 was confirmed by a presence of SARS‐CoV‐2 ribonucleic acid in the respiratory specimens detected by a qualitative, real‐time reverse transcription‐polymerase chain reaction. The study focused on the clinical course and management of our cases. Results: A family cluster of four laboratory‐confirmed COVID‐19 patients, one of those carried an underlying kidney transplant (KT) receiving immunosuppressants. Clinical presentation and severity of our case series are variable depending on each individual immune status. By far, a KT recipient seems to develop more severity despite antiviral therapy, cessation of immunosuppressant, and aggressive intensive care support. Conclusion: Our case series plausibly affirmed a person‐to‐person transmission and potentially severe disease in the transplant population. Clinicians who are encountering with transplant recipients should be aware of possible transmission among family members. Abstract : A family cluster of four laboratory‐confirmed COVID‐19 patients. Our case series plausibly affirmed a person‐to‐person transmission and potentially severe disease in the transplant population. Clinicians who are encountering with transplant recipients should be aware of possible transmission among family members.